@stephanjoubert: Tweeting the gospel aphoristically - Jan A. van den Berg (AOSIS, 2021)
This contribution focusses on some of the digital theological expressions of Stephan Joubert from an auto-ethnographic angle. Orientating from a practical theology perspective, I have chosen the social media platform Twitter, and more specifically the @stephanjoubert domain, as source to chart some significant tweet expressions for the purpose of describing the character and value of an aphoristic theology. In order to do so, I have used some randomly selected tweets of Stephan Joubert, spanning the period 2020–2021, which express aspects of a relevant contemporary ecclesiology. Against the backdrop of the disastrous impact of the COVID-19 pandemic as well as some important dates on the Christian calendar (Easter and Christmas), I specifically emphasise the significance of the formulation of an aphoristic theology using amongst other markers of simplicity, contextuality and relevance.